ANALISIS EFEKTIFITAS PROGRAM PENYALURAN RASKIN DI KAMPUNG KARANG SENANG DISTRIK KUALA KENCANA KABUPATEN MIMIKA - Natalia Silolongan; Try Apriyono (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2017)
The aims of this research is to know how well the extent of the effectiveness of the distribution of rice for poor person in Karang Senang village, district of Kuala Kencana, Mimika Regency. This research was executed in Karang Senang Village in August to December 2014. This research uses secondary data, the time series data in the years of 2002 to 2013. Collecting of data was done through questioner and documentation. The data was analyzed by effectiveness analysis. The result of research showed that the distribution of rice for poor person program in Karang Senang Village, Kuala Kencana District have been effective.